Scale Drop Disease Virus (SDDV) and Lates calcarifer Herpes Virus (LCHV) Coinfection Downregulate Immune-Relevant Pathways and Cause Splenic and Kidney Necrosis in Barramundi Under Commercial Farming Conditions - Domingos, Jose A.; Shen, Xueyan; Terence, Celestine; Senapin, Saengchan; Dong, Ha Thanh; Tan, Marie R.; Gibson-Kueh, Susan; Jerry, Dean R. (Frontiers in Genetics, 2021)
Marine farming of barramundi (Lates calcarifer) in Southeast Asia is currently severely affected by viral diseases. To better understand the biological implications and gene expression response of barramundi in commercial farming conditions during a disease outbreak, the presence of pathogens, comparative RNAseq and histopathology targeting multiple organs of clinically “sick” and “healthy” juveniles were investigated. Co-infection of scale drop disease virus (SDDV) and Lates calcarifer herpes virus (LCHV) were detected in all sampled fish, with higher SDDV viral loads in sick than in healthy fish. Histopathology showed that livers in sick fish often had moderate to severe abnormal fat accumulation (hepatic lipidosis), whereas the predominant pathology in the kidneys was moderate to severe inflammation and glomerular necrosis. The spleen was the most severely affected organ, with sick fish presenting severe multifocal and coalescing necrosis. Principal components analysis (PC1 and PC2) explained 70.3% of the observed variance and strongly associated the above histopathological findings with SDDV loads and with the sick phenotypes, supporting a primary diagnosis of the fish being impacted by scale drop disease (SDD). Extracted RNA from kidney and spleen of the sick fish were also severely degraded likely due to severe inflammation and tissue necrosis, indicating failure of these organs in advanced stages of SDD. RNAseq of sick vs. healthy barramundi identified 2,810 and 556 differentially expressed genes (DEGs) in the liver and muscle, respectively. Eleven significantly enriched pathways (e.g. phagosome, cytokine-cytokine-, ECM-, neuroactive ligand-receptor interaction, calcium signaling, MAPK, CAMs, etc.), and gene families (e.g. tool-like receptor, TNF, lectin, complement, interleukin, chemokine, MHC, B and T cells, CD molecules, etc.) relevant to homeostasis, innate and adaptive immunity were mostly downregulated in sick fish. These DEGs and pathways, also previously identified in L. calcarifer as general immune responses to other pathogens and environmental stressors, suggest a failure of the clinically sick fish to cope and overcome the systemic inflammatory responses and tissue degeneration caused by SDD.